Anthropometric and Biochemical Profile of Children and Adolescents with Chronic Kidney Disease in a Predialysis Pediatric Interdisciplinary Program - Vanessa R. Silva; Cristina B. Soares; Juliana O. Magalhães; Isabella Peixoto de Barcelos; Debora C. Cerqueira; Ana Cristina Simões e Silva; Eduardo A. Oliveira (The Scientific World Journal)
This is longitudinal retrospective observational cohort study that evaluated anthropometric and biochemical variables of children and adolescents admitted to a Predialysis Interdisciplinary Management Program (PDIMP) responsible for the follow-up of children and adolescents at stages 2 to 4 of chronic kidney disease (CKD) at a tertiary center. One hundred thirty-eight patients with CKD on predialysis treatment with median age at admission of 9 years and the median follow-up time of 5 years were evaluated. Seventy-four (53%) had CKD stage 3 at admission and 70 (51%) reached CKD stage 5 at the end of the follow-up. There was no significant difference between the mean initial and final hemoglobin and serum albumin. However, the final serum bicarbonate presented a significant improvement. Analyses stratified according to clinical variables of interest showed a significant improvement in body mass index (BMI) Z score, especially in the subgroup of children admitted under two years of age. In relation to stature-for-age Z score, data show a significant improvement in stature SD at the end of the study. In conclusion, the present study showed improvement of nutritional status of CKD patients and that the deterioration of renal function was not correlated with BMI-for-age Z score.